The Effectiveness of the Eco-Pesantren Program in Creating Economic Value Through Green Product Development at Baitul Hikmah Islamic Boarding School, Tempurejo, Jember - Suprianik; Mariyah Ulfah (Journal of Creative Power and Ambition (JCPA), 2026)
This study examines the implementation of the eco-pesantren concept in integrating green economy principles at Pondok Pesantren Baitul Hikmah Tempurejo, Jember. Environmental degradation, climate change, and socioeconomic inequality have increased the need for sustainable development based on Islamic values, where humans are regarded as khalifah fil-ardh with the responsibility to preserve nature. Using a descriptive qualitative approach, data were collected through observations, in-depth interviews, documentation, and source triangulation to ensure credibility. The findings indicate that the eco-pesantren program effectively integrates environmental education into the pesantren curriculum, promotes waste management practices, and develops students’ entrepreneurial skills through the Santri Tani Milenial program. Green products, including organic agricultural products and recycled goods, contribute to strengthening the pesantren’s economic independence while equipping students with practical competencies in environmentally friendly agribusiness. Furthermore, partnerships with local communities, government institutions, and business stakeholders support the sustainability of green enterprises by providing financial assistance, technical guidance, and market access. These findings demonstrate that the eco-pesantren model offers a sustainable framework for integrating Islamic education, environmental stewardship, and local economic development.